The structure of the human c-fes/fps proto-oncogene. - Roebroek, A J (1985)
We have determined the complete nucleotide sequence of a human DNA fragment of approximately 13 kbp, which was shown by Southern blot analysis to contain the entire v-fes/fps cellular homolog. The v-fes/fps homologous sequences were dispersed over 11 kbp in 18 interspersed segments which were flanked by splice junctions. Fusion of these segments created a DNA fragment in which coding regions similar to those observed in the viral oncogenes v-fes of the Gardner-Arnstein (GA) and Snyder-Theilen (ST) strains of feline sarcoma virus and v-fps found in Fujinami sarcoma virus could be identified. A potential initiation site in the first exon was found. About 200 nucleotides downstream of a translational stop codon in the v-fes/fps homologous region, a poly(A) addition signal was identified. The deduced amino acid sequence has a molecular weight of 93 390 dalton resembling NCP92, the recently described human c-fes/fps product. The topography of human c-fes/fps appeared to resemble that of chicken c-fps.